Surgical resection of a thymoma developed in a case with isolated persistent left superior vena cava. (September 2022) - Hato, Tai; Fukuda, Hiroki; Mitsutomo, Kohno; Nakayama, Mitsuo
Abstract: Introduction: Persistent left superior vena cava (PLSVC) is one of the most common vascular abnormalities in the chest. In approximately 10 % of cases, the right superior vena cava is missing, which is called isolated persistent left superior vena cava (IPLSVC). Presentation of case: The case is an 85 years-old female. An anterior mediastinal tumor was accidentally revealed when the patient was admitted after a traffic accident. As the tumor became larger within four months, a thymectomy was planned. The anterior mediastinal tumor was in front of the ascending aorta, which was close to the confluence of the left and right brachiocephalic veins in normal anatomy. However, in this case, the right superior vena cava was missing, and the right brachiocephalic vein flowed into the left superior vena cava by the chest computed tomography. Preoperative examinations found no accompanying cardiac abnormality. Robot-assisted thymectomy was performed. No tumor infiltration was observed in the right brachiocephalic vein. No abnormality was found in either phrenic nerve. The tumor could be safely resected, and her postoperative course was uneventful. The pathological diagnosis was a thymoma. Discussion: A case of thymectomy with IPLSVC is quite rare. A careful observation of the preoperative computed tomography images helps to diagnose IPLSVC. Technically, thymectomy was not much different from normal, other than the reversed location of the veins. However, it should be noted that IPLSVC cases may have cardiac malformations. Conclusion: Thymectomy for thymoma with IPLSVC can be safely performed when the left and right veins are reversed. Highlights: Persistent left superior vena cava (PLSVC) is the most common anatomical abnormality that occurs in the thoracic vasculature. Most PLSVCs are so-called double SVCs that coexist with the right SVC, and isolated PLSVCs (IPLSVCs) that exist only on the left are rare. The patient was asymptomatic and had no complications of cardiac malformations. The IPLSVC flowed into the right atrium from the dilated coronary sinus via the vein of Marshall. IPLSVC with thymoma is extremely rare. The tumor's location was where the confluence of the left and right brachiocephalic veins would be if the anatomy was normal. In this case, the resection was safely completed despite the anatomical abnormality.